The new dynamics and economics of cooperative collection development : papers presented at a conference hosted by the Center for Research Libraries, cosponsored by the Association of Research Libraries with the support of the Gladys Kreible Delmas Foundation, November 8-10, 2002, Atlanta, Georgia /: papers presented at a conference hosted by the Center for Research Libraries, cosponsored by the Association of Research Libraries with the support of the Gladys Kreible Delmas Foundation, November 8-10, 2002, Atlanta, Georgia. ([2018?]) - Unknown
No abstract available